SUN-485 Combined Treatment with Laser Ablation and Tyrosin Kinase Inhibitors. a Novel Multimodality Approach to Locally Advanced Thyroid Cancer? - Papini, Enrico (J Endocr Soc, 2020)
Background. Direct loco-regional treatments are considered for local control of cervical metastasis of thyroid cancer. In our feasibility study, laser ablation was employed for initial debulking of an unresectable radioiodine-refractory thyroid cancer in a combined treatment with tyrosin kinase inhibitors (TKI). Clinical case. On June 2016, a 69-year-old woman underwent partial resection of a papillary thyroid cancer with extensive tracheal infiltration. On August 2016, whole body scan performed after 131-I treatment (8140 MBq) demonstrated nearly absent thyroid bed uptake. Due to progressive increase of the cervical mass, the patient experienced dysphonia and dysphagia and, after multidisciplinary consultation, was treated with laser ablation (LTA). After local anesthesia, two 300 nm fiberoptics were inserted into the lesion through 21G spinal needles. Two illuminations with 4-watt output power and 3600 Joules energy delivery were peformed with a diode-laser source. LTA resulted in rapid mass volume decrease (28 x12 x16 mm, 2.8 mL, vs 52 x 29 x 29 mm, 22.7 mL) and improvement of pressure symptoms that lasted 6 months. In May 2017, due to initial regrowth of the tumor mass, the patient started therapy with Lenvatinib, at 10-24 mg/day. The cervical tumor burden remained controlled until April 2019, when occurred rapid disease progression and death of the patient. Discussion. These preliminary results suggest that locally-advanced unresectable and radioiodine-refractory thyroid tumors can be managed with preliminary LTA mass debulking, for rapid control of local disease, followed by long-term TKI treatment. References. Mauri G et al. Cardiovasc Intervent Radiol. 2016 Jul; 39(7):1023-30; Park KW et al. Ann Surg Oncol 2011; 18:2564-2568. Schlumberger M et al. NEJM 2015 12; 372(7):621-30.